2018
DOI: 10.1017/wsc.2018.4
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Management Options onStrigaInfestation and Maize Grain Yield in Kenya

Abstract: The parasitic purple witchweed [Striga hermonthica (Del.) Benth.] is a serious constraint to maize production in sub-Saharan Africa, especially in poor soils. Various Striga spp. control measures have been developed, but these have not been assessed in an integrated system. This study was conducted to evaluate a set of promising technologies for S. hermonthica management in western Kenya. We evaluated three maize genotypes either intercropped with peanut (Arachis hypogaea L.), soybean [Glycine max (L.) Merr.]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
50
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 32 publications
1
50
1
Order By: Relevance
“…Maize is a source of both carbohydrates and protein for millions of people in ESA. Maize production in this region is affected by several biotic stresses including insect pests (Goergen, Kumar, Sankung, Togola, & Tamò, 2016; Kfir, Overholt, Khan, & Polaszek, 2002; Mugo et al., 2004), virus and foliar diseases (Kyetere et al., 1999; Mahuku et al., 2015; Marenya et al., 2018; Martin & Shepherd, 2009; Prasanna et al., 2020; Wangai et al., 2012), and parasitic weeds especially Striga hermonthica (Kanampiu et al., 2018). The major foliar diseases of economic importance in the mid‐altitude and highland ecologies of ESA are northern corn leaf blight (NCLB) caused by Exserohilum turcicum (Pass.)…”
Section: Introductionmentioning
confidence: 99%
“…Maize is a source of both carbohydrates and protein for millions of people in ESA. Maize production in this region is affected by several biotic stresses including insect pests (Goergen, Kumar, Sankung, Togola, & Tamò, 2016; Kfir, Overholt, Khan, & Polaszek, 2002; Mugo et al., 2004), virus and foliar diseases (Kyetere et al., 1999; Mahuku et al., 2015; Marenya et al., 2018; Martin & Shepherd, 2009; Prasanna et al., 2020; Wangai et al., 2012), and parasitic weeds especially Striga hermonthica (Kanampiu et al., 2018). The major foliar diseases of economic importance in the mid‐altitude and highland ecologies of ESA are northern corn leaf blight (NCLB) caused by Exserohilum turcicum (Pass.)…”
Section: Introductionmentioning
confidence: 99%
“…Among the more than 40 known Striga species worldwide, Striga hermonthica [Del.] Benth is the most destructive, harmful, and widespread in SSA, causing significant yield loss in cereals [ 11 , 12 ]. S. hermonthica is a root hemiparasite plant that parasitizes its host and extracts water and essential nutrients from it, resulting in stunting, wilting, chlorosis, reduction in yield, and death of the host.…”
Section: Introductionmentioning
confidence: 99%
“…It is thus suggested that the use of improved cultivars and appropriate sowing dates can help to control Striga infestation (Ekeleme et al, 2011). To reduce losses in maize yield due to Striga infestation, the use of tolerant or resistant varieties has been suggested (Kanampiu et al, 2018). Progress has been made by researchers in maize breeding in the area of identifying genotypes that are tolerant or resistant to Striga (Kanampiu et al, 2018;Adesina and Akinwale, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…To reduce losses in maize yield due to Striga infestation, the use of tolerant or resistant varieties has been suggested (Kanampiu et al, 2018). Progress has been made by researchers in maize breeding in the area of identifying genotypes that are tolerant or resistant to Striga (Kanampiu et al, 2018;Adesina and Akinwale, 2014). It is practicable and compatible with the low-cost input technology of the resource-poor farmer (Kamara et al, 2014).…”
Section: Introductionmentioning
confidence: 99%